Joint continuity of K_h C-functions with values in moore spaces - Maslyuchenko, V. K.; Mykhailyuk, V. V.; Filipchuk, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We introduce a notion of a categorical cliquish mapping and prove that, for each K_h C-mapping f : X × Y → Z (here, X is a topological space, Y is a first countable space, and Z is a Moore space) with categorical cliquish horizontal y-sections f_y , the sets C_y (f) are residual G_δ-sets in X for each y Y.